Model Prediksi Liku Kalibrasi Menggunakan Pendekatan Jaringan Saraf Tiruan (ZST) (Studi Kasus : Sub DAS Siak Hulu) - Mahyudin, Mahyudin; Suprayogi, Imam; Trimaijon, Trimaijon (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The purpose of this research is to predict the rating curve equation on the site Pantai Cermin Sub-watershed Siak Hulu Siak River in 2009. This is based due to the unavailability of rating curve equation on the site Pantai Cermin Sub-watershed Siak Hulu in 2009 until 2012 so hopefully this research can be used as an alternative method for determining the rating curve equation turns more quickly and accurately. This research was conducted using an artificial neural network approach to the backpropagation algorithm. Configuration of network model used is the single input and single output. This approach uses auxiliary program that is Matlab 7.7.0.471 (R2008b). Results of this research showed that the artificial neural network model results of training, testing and validation have a very good level of correlation with the value of R 0.92996, 0.94469 and 0.97513. The rating curve equation for 2009 is Q = 22.93 x H1.265 with the level of correlation R = 0.9975. Keywords: rating curve, artificial neural network, backpropagation, siak hulu.